Особливості автоматизації параметричного моделювання динаміки роторів відцентрових компресорів за допомогою різних моделей - Мартиненко, Геннадій Юрійович; Марусенко, Олексій Миколайович (НТУ "ХПІ", 2015)
Проведено аналіз власних частот і форм коливань моделей ротора, побудованих і розрахованих за допомогою програмних комплексів машинобудівного призначення. Розроблено програмний продукт для побудови моделей ротора, проведення розрахунків їх динамічних характеристик з наочним представленням результатів. Програма забезпечує зв'язок з макросом і програмним комплексом для проведення розрахунку, а також з браузером для перегляду отриманих результатів.

The analysis of natural frequencies and mode shapes of the rotor models, constructed and calculated at software systems of engineering applications. The work confirmed that the use of elastic supports is appropriate. The software product allow building a model of the rotor, carry out calculations of its dynamic characteristics with a visual representation of the results. The program provides a link with the macro and program complex for calculation and with browser to view the results and allows you to change the required parameters of the rotor. Program facilitates the analysis of the dynamic behavior of the rotor, and reduces the time spent in the calculation model and foranalys results.
Features of automation parametric modeling the dynamics of the rotors of centrifugal compressors with different models
Keywords: магнітні підшипники; критичні швидкості; ПК; перекачка газу; magnetic bearings; critical speeds